ANALISIS MARKET OVERREACTION PADA SAHAM PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rachmawati, Eka Nuraini; Saputra, Randi; Penjaitan, Kristina (Program Studi Manajemen, 2023)
This study aims to determine whether there is market overreaction on the Indonesia Stock Exchange during the research period from 2017 to 2020. The population in this study are LQ45 index component companies listed on the Indonesia Stock Exchange. The sample in this study was obtained by purposive sampling method, namely as many as 30 companies. Market overreaction is measured by abnormal returns and is shown by the Average Cumulative Abnormal Return (ACAR) portfolio of losers outperforming the Average CAR portfolio of winners. The results showed that the loser portfolio's Average CAR could not outperform the winner's portfolio. Based on the research results, it can be concluded that there is no market overreaction to the LQ45 index company shares on the Indonesia Stock Exchange.